2022
DOI: 10.3390/ijms23095098
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcriptomic and Protein Array Cytokine Profiling of Human Stem Cells from Dental Apical Papilla Modulated by Oral Bacteria

Abstract: Stem cells from the apical papilla (SCAP) are a promising resource for use in regenerative endodontic treatment (RET) that may be adversely affected by oral bacteria, which in turn can exert an effect on the success of RET. Our work aims to study the cytokine profile of SCAP upon exposure to oral bacteria and their supernatants—Fusobacterium nucleatum and Enterococcus faecalis—as well as to establish their effect on the osteogenic and immunogenic potentials of SCAP. Further, we target the presence of key prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 70 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…In our past studies, we have shown how short-term modulation of SCAP by bacteria can affect their viability, immune response, and gene expression for osteogenesis and dentinogenesis ( Razghonova et al., 2022 ; Zymovets et al., 2022 ). However, to assess whether bacterial influence alone, without the presence of osteo/dentinogenic induction medium, can stimulate SCAPs mineralization and thus influence their differentiation potential, a minimum of 21 days of bacterial exposure is required, which is the necessary duration for cell differentiation ( Abuarqoub et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our past studies, we have shown how short-term modulation of SCAP by bacteria can affect their viability, immune response, and gene expression for osteogenesis and dentinogenesis ( Razghonova et al., 2022 ; Zymovets et al., 2022 ). However, to assess whether bacterial influence alone, without the presence of osteo/dentinogenic induction medium, can stimulate SCAPs mineralization and thus influence their differentiation potential, a minimum of 21 days of bacterial exposure is required, which is the necessary duration for cell differentiation ( Abuarqoub et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The BDNF, GM-CSF, and VEGF-A, were chosen for their important role in osteo/odontogenic cells differentiation and regeneration ( Saito et al., 2011 ; Kolar et al., 2017 ; Liu et al., 2018 )). The pro-inflammatory markers—IL-8, IL-6, MCP-1, and IL-17A were selected based on the results of previous studies, indicating the upregulation of these markers in SCAPs under bacterial influence ( Razghonova et al., 2022 ; Zymovets et al., 2022 ) as well as IL-1a and IL-1β, as they are involved in innate pro-inflammatory response ( Dinarello, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Fusobacterium nucleatum triggers pro-inflammatory chemokine and cytokine generation in SCAPs while Enterococcus faecalis inhibits the same [73]. In addition, E. faecalis, but not F. nucleatum, can downregulate the expression levels of key proteins in Wnt/β-Catenin and NF-κB signaling pathways [76].…”
Section: Interactions Between Scaps and Oral Bacteriamentioning
confidence: 99%